Human-crocodile conflict (Nile crocodile: Crocodylus niloticus) in the Okavango Delta, Botswana - Thomas, Georgina Diane (Stellenbosch : Stellenbosch University, 2012)
Thesis (MSc)--University of Stellenbosch, 2006.